KEMAMPUAN MAHASISWA PGSD FKIP UNIVERSITAS RIAU DALAM MENULIS SURAT RESMI - Otang Kurniaman; Muhammad Nailul Huda; Eddy Noviana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The research is descriptive quantitative research conducted to look at the ability of students in the class of 2014 to write a formal letter, a technique in data collection in the form of observation results by student writing an official letter PGSD FKIP Riau University class of 2014 instrument validity of his research has been validated through expert judgment. The sample in this study as masy as 46 students of primary school teaching force in 2014 the Faculty of Education, University of Riau. The ability of students PGSD FKIP Riau University after analyzed using categories, from 12 aspects outlined in the instrument observation sheets, getting the results that the completeness aspect predicate section of the letter simply by percentage (65, 76%), while the writing aspect letterhead good predicate with percentage (79,89%), while the aspect of writing an official letter dated sufficient predicate with percentage (54, 35%), while the aspect of writing about the letter predicate less by percentage (35, 87%), while the writing aspect of the destination address with sufficient predicate persentage (59, 78%), while the aspect of writing greeting predicate simply by percentage (54,35%), while the contents of the letter writing aspect predicate simply by percentage (63,04%), while the writing aspect regards predicate cover less by percentage (42, 93%), while in writing the name of the sender predicate very well with percentage (98, 91%), while the use of indonesioan predicate either by percentage (71, 74%), while in the aspect of the preparation of sufficient premises sentence predicate percentage (58,15%) and on aspects of the form or neatness letter predicate simply by percentage (58, 15%). From the results, the average overall percentage of 61, 91% is obtained with neough categories, this suggests that the ability of students PGSD class of 2014 FKIP University of Riau still low in writing a formal letter.